Leadership in a school context: how leadership styles are associated with leadership outcomes - Hariri, Hasan (Goodwood Publishing, 2020)
Purpose: This paper aims at examining how principal leadership styles are associated with leadership outcomes in an Indonesian school context. Research Methodology: Survey data were collected using MLQ 5X-Short and a demographic questionnaire completed by 475 teachers in 36 junior high schools in the Province of Lampung, Indonesia. With the help of SPSS version 22, the collected data were initially analyzed using descriptive statistics and then Pearson product-moment correlation. Results: Results show that transformational and transactional leadership styles are positively and significantly associated with the leadership outcomes, but the laissez-faire leadership style is negatively and significantly associated with the leadership outcomes. Limitations: This paper used a quantitative research approach and is acknowledged for being limited to using the survey questionnaire so that it could not explain why and how principal leadership styles affect such leadership outcomes. Contribution: This paper theoretically and practically contributes to the body of knowledge, particularly concerning leadership styles and their outcomes. Keywords: School leadership, Leadership outcomes, Principal, teacher How to cite: Hariri, Hasan. (2020). Leadership in a School Context: How Leadership Styles Are Associated with Leadership Outcomes. International Journal of Financial, Accounting, and Management, 2(2), 159-170.